2021
DOI: 10.3389/fphar.2021.640297
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of An-Gong-Niu-Huang Wan Pre-treatment Against Experimental Cerebral Ischemia Injury via Regulating GSK-3β/HO-1 Pathway

Abstract: An-Gong-Niu-Huang Wan (AGNHW), a famous formula in traditional Chinese medicine, has been clinically used for centuries for treating cerebral diseases, but the protective effects of pre-treatment with AGNHW on cerebral ischemia have not yet been reported. The present study aimed to test such protective effects and elucidate the underlying mechanisms on cerebral ischemia in rats by phenotypic approaches (i.e. including the neurological functional score, cerebral infarct area, neuron apoptosis, and brain oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…MCAO was induced after the third administration of OA as described in our previous report [36]. Briefly, rats were anesthetized by 3% isoflurane inhalation (1.5 L/min).…”
Section: Mcao Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…MCAO was induced after the third administration of OA as described in our previous report [36]. Briefly, rats were anesthetized by 3% isoflurane inhalation (1.5 L/min).…”
Section: Mcao Proceduresmentioning
confidence: 99%
“…Neurological function was analyzed 6 days after reperfusion using the Zea-Longa score, as described previously [36]. The Zea-Longa score ranges from 0 to 4 (0: no obvious impairment; 1: inextensibility of the contralateral forepaw; 2: circling to the contralateral side; 3: leaning to the contralateral side; 4: disability to walk spontaneously).…”
Section: Neurological Deficit Assessment and Brain Tissue Collectionmentioning
confidence: 99%
“…Experimental studies revealed that BHD and TXL could alleviate cerebral I/R injury and exert protective effects on the BBB ( Liu et al, 2013 ; Chen et al, 2019 ). In studies about the therapeutic efficacy of TCM compound medicines or extracts, such as BHD and TXL mentioned above for cerebral I/R injury, drug administration for 3–7 days starting before MCAO is the common means to enhance intervention effects ( Liu et al, 2013 ; Yu et al, 2018 ; Chen et al, 2019 ; She et al, 2019 ; Zheng et al, 2019 ; Zhang S. et al, 2021 ). Accordingly, based on these literatures, we select YZFDF pretreatment to carry out the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The Angong Niuhuang Pill (ANP) is a well-known classical prescription of traditional Chinese medicine (TCM), widely used for the management of acute cerebrovascular diseases such as ischemia stroke, intracerebral hemorrhage, and traumatic brain damage [ 17 , 18 ], having the role to prevent neural apoptosis and neurological deficits [ 19 ]. Meanwhile, its protective effects on tight junction proteins have been documented [ 20 ].…”
Section: Introductionmentioning
confidence: 99%